2020
DOI: 10.1097/hcr.0000000000000532
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Knowledge and Attitudes of Cardiology Fellows

Abstract: Purpose: Cardiac rehabilitation (CR) is underutilized with only 8-31% of eligible patients participating. Lack of referral and lack of physician endorsement are well-known barriers to participation. Physicians who lack insights regarding CR are less likely to refer patients and recommend it. Cardiology fellows are early career physicians who spend a significant amount of time treating patients eligible for CR. At one institution's cardiology fellowship program, we sought to assess fellow attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…These findings suggest that structured resident education on CR is effective in addressing physician knowledge gaps and has a role in changing referral habits in trainees. A previous study of cardiology fellowship trainees had similar findings of low CR knowledge scores and poor understanding of the physician referral processes [18] . Further, the majority of the internal medicine residents reported that they did not receive any formal education on CR over the past 1 year during their residency training.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings suggest that structured resident education on CR is effective in addressing physician knowledge gaps and has a role in changing referral habits in trainees. A previous study of cardiology fellowship trainees had similar findings of low CR knowledge scores and poor understanding of the physician referral processes [18] . Further, the majority of the internal medicine residents reported that they did not receive any formal education on CR over the past 1 year during their residency training.…”
Section: Discussionmentioning
confidence: 65%
“…Knowledge questions consisted of multiple correct and incorrect possibilities and were adapted from a survey used in a prior study of cardiology fellowship trainees [18] . Survey questions were replicated with the exception of demographic questions, which were adjusted to account for the difference in level of training.…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest that referral seems to be less affected by the individual patient characteristics e.g. comorbidity, and might instead be more related to organizational elements and CR knowledge and endorsement from health care professionals (12,37,38).…”
Section: Discussionmentioning
confidence: 75%
“…Barriers to CR participation and adherence are numerous and can include the following: lack of local CR programs, lack of referral and enrollment, transportation, physical limitations, competing demands, comorbidities, living alone, fear of exercise, and cost, among others. [8][9][10][11][12][13][14] The most vulnerable populations that are underrepresented in CR programs include older adults, women, ethnic minorities, veterans, and individuals with low socioeconomic status representing many social determinants of health (SDOH). 6,8,10,13,[15][16][17] Importantly, the current pandemic has posed a significant barrier to CR participation as many of the already limited number of center-based CR programs in the US have suspended or reduced services to limit contagion.…”
mentioning
confidence: 99%